Genetic Divergence and Evolutionary Relationship in Fejervarya cancrivora from Indonesia and Other Asian Countries Inferred from Allozyme and MtDNA Sequence Analyses - Kurniawan, N.; Islam, M.M.; Djong, T.H.; Igawa, T.; Belabut, D.M.; Yong, Hoi Sen; Wanichanon, R.; Khan, M.M.R.; Iskandar, D.T.; Nishioka, M.; Sumida, M. (Zoological Society of Japan, 2010)
To elucidate genetic divergence and evolutionary relationship in Fejervarya cancrivora from Indonesia and other Asian countries, allozyme and molecular analyses were carried out using 131 frogs collected from 24 populations in Indonesia, Thailand, Bangladesh, Malaysia, and the Philippines. In the allozymic survey, seventeen enzymatic loci were examined for 92 frogs from eight representative localities. The results showed that F. cancrivora is subdivided into two main groups, the mangrove type and the large- plus Pelabuhan ratu types. The average Nel's genetic distance between the two groups was 0.535. Molecular phylogenetic trees based on nucleotide sequences of the 16S rRNA and Cyt b genes and constructed with the ML, MP, NJ, and BI methods also showed that the individuals of F. cancrivora analyzed comprised two clades, the mangrove type and the large plus Pelabuhan ratu / Sulawesi types, the latter further split into two subclades, the large type and the Pelabuhan ratu / Sulawesi type. The geographical distribution of individuals of the three F. cancrivora types was examined. Ten Individuals from Bangladesh, Thailand, and the Philippines represented the mangrove type; 34 Individuals from Malaysia and Indonesia represented the large type; and 11 individuals from Indonesia represented the Pelabuhan ratu / Sulawesi type. Average sequence divergences among the three types were 5.78–10.22% for the 16S and 12.88–16.38% for Cyt b. Our results suggest that each of the three types can be regarded as a distinct species.